Partisan Politics and Intergovernmental Transfers in India - Khemani, Stuti (World Bank, Washington, DC, 2014)
Recently there has been a surge in international empirical evidence that national policymakers allocate resources across regions based on political considerations, in addition to any normative considerations of equity and efficiency. In order to mitigate these political compulsions, several federations around the world have attempted to create independent constitutional bodies that are responsible for determining federal transfers to subnational jurisdictions. The author tests whether constitutional rules indeed make a difference in curbing political influence by contrasting the impact of political variables on two types of intergovernmental transfers to states in the Indian federation over a period of time, 1972-95. The pattern of evidence shows that transfers, whose regional distribution is determined by political agents, usually provide greater resources to state governments that are politically affiliated with the national ruling party and are important in maximizing the party's representation in the national legislature. But the political effect on statutory transfers, determined by an independent agency with constitutional authority, is strikingly contrary, with greater resources going to unaffiliated state governments. The author argues that this contrasting evidence indicates that constitutional rules indeed restrict the extent to which partisan politics can affect resources available to subnational governments.